HIV/AIDS in the Zimbabwe Defence Force: a civil society perspective - Matchaba-Hove, Reginald (Institute for Security Studies, 2016)
This chapter constitutes a civil society perspective of HIV/AIDS and the military in Zimbabwe. A brief background is provided outlining the country’s geographic and demographic profile, political economy, aspects of food supply and civil society’s concern about the militarisation of civilian institutions. A detailed outline of the epidemiology of HIV/AIDS in Zimbabwe is provided, including Zimbabwe’s response to the pandemic, followed by some discussion of recent results that reflect a decline in national HIV prevalence.